The role of school leadership in promoting socio-emotional competencies: Evidence from a bibliometric study - Cristóvão, Ana Maria; Valente, Sabina; Rebelo, Hugo Ricardo (Aprender, 2025)
In this article, we discuss the role of school leaders in promoting social and emotional skills in an educational context characterised by pedagogical, organisational, and emotional challenges. We begin with a holistic and humanistic view of education, advocating for pedagogical and transformative leadership as the most effective approach to promoting safe, caring, and inclusive school environments. The study aimed to analyse how school leadership contributes to the development of students’ social and emotional skills. Bibliometrics and content analysis were used as methodologies in studies identified on the Google Scholar, Scopus, and Web of Science platforms. After selection, nine publications met the inclusion criteria. About half of the studies highlight the relevance of leaders’ social-emotional learning skills for more effective practices (e.g., empathy, social awareness, and responsible decision-making). There is consistent evidence of an impact on the school climate and culture. Barriers remain: insufficient preparation of leaders, pressure for academic results, and socio-political constraints. We conclude that school leaders play a crucial role in the sustainable integration of social-emotional learning. It is essential to rethink leadership training by incorporating social-emotional skills and support policies that consolidate educational environments that promote well-being and success.